The Social Distancing Imposed To Contain COVID-19 Can Affect Our Microbiome: a Double-Edged Sword in Human Health - Célia P. F. Domingues; João S. Rebelo; Francisco Dionisio; Ana Botelho; Teresa Nogueira (mSphere, 2020)
ABSTRACT Hygienic measures imposed to control the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and contain COVID-19 have proven effective in controlling the pandemic. In this article, we argue that these measures could impact the human microbiome in two different and disparate ways, acting as a double-edged sword in human health. New lines of research have shown that the diversity of human intestinal and oropharyngeal microbiomes can shape pulmonary viral infection progression. Here, we suggest that the disruption in microbial sharing, as it is associated with dysbiosis (loss of bacterial diversity associated with an imbalance of the microbiota with deleterious consequences for the host), may worsen the prognosis of COVID-19 disease. In addition, social detachment can also decrease the rate of transmission of antibiotic-resistant bacteria. Therefore, it seems crucial to perform new studies combining the pandemic control of COVID-19 with the diversity of the human microbiome.